Draft Ninth Five Year Plan 1997-2002 Tripura Part-III - Planning Commission (Planning Commission, 1997)
Sub-Sector wise Outlay and Expenditure Ninth Plan 1997-2002 Proposed Outlays Ninth Plan 1997-2002 Proposed Outlays (Scheme wise) Physical Targets and Achievements Minimum Needs Programmes/Basic Minimum Services Central/ Centrally Sponsored Schemes.
Government of Tripura Planning and Coordination Department
Government of Tripura Planning and Coordination Department